Orbital period analyses for two cataclysmic variables: UZ Fornacis and V348 Puppis inside the period gap - Dai, Z. B. (2010)
Four new CCD eclipse timings of the white dwarf for polar UZ Fornacis and six updated CCD mid-eclipse times for SW-Sex-type nova-like V348 Puppis are obtained. Detailed O-C analyses are made for both cataclysmic variables (CVs) inside the period gap. Orbital period increases at a rate of 2.63(±0.58) × 10-11 s s -1 for UZ For and 5.8(±1.9) × 10-12 s s -1 for V348 Pup, respectively, are discovered in their new O-C diagrams. However, conservative mass transfer from the secondary to the massive white dwarf cannot explain the observed orbital period increases for both CVs, which are regarded as part of modulations at longer periods. Moreover, the O-C diagram of UZ For shows a possible cyclical change with a period of 23.4(±5.1) yr. To explain the observed cyclical period changes in UZ For, both mechanisms of magnetic activity cycles in late-type secondaries and the light travel-time effect are regarded as probable causes. Not only does the modulation period of 23.4 yr obey the empirical correlation between Pmod and Ω, but also the estimated fractional period change δP/P ~ 7.3 × 10-7 displays a behaviour similar to that of CVs below the period gap. On the other hand, a calculation for the light travel-time effect implies with a high confidence level that the tertiary component in UZ For may be a brown dwarf, when the orbital inclination of the third body is larger than 16°.